Regulation of myeloproliferation and M2 macrophage programming in mice by Lyn/Hck, SHIP, and Stat5 - Xiao, Wenbin (American Society for Clinical Investigation, 2008)
The proliferation and differentiation of hematopoietic stem cells (HSCs) is finely regulated by extrinsic and intrinsic factors via various signaling pathways. Here we have shown that, similar to mice deficient in the lipid phosphatase SHIP, loss of 2 Src family kinases, Lyn and Hck, profoundly affects HSC differentiation, producing hematopoietic progenitors with increased proliferation, reduced apoptosis, growth factor–independent survival, and skewed differentiation toward M2 macrophages. This phenotype culminates in a Stat5-dependent myeloproliferative disease that is accompanied by M2 macrophage infiltration of the lung. Expression of a membrane-bound form of SHIP in HSCs lacking both Lyn and Hck restored normal hematopoiesis and prevented myeloproliferation. In vitro and in vivo studies suggested the involvement of autocrine and/or paracrine production of IL-3 and GM-CSF in the increased proliferation and myeloid differentiation of HSCs. Thus, this study has defined a myeloproliferative transformation-sensitive signaling pathway, composed of Lyn/Hck, SHIP, autocrine/paracrine cytokines, and Stat5, that regulates HSC differentiation and M2 macrophage programming.